1999
DOI: 10.1116/1.591091
|View full text |Cite
|
Sign up to set email alerts
|

Charging and discharging of electron beam resist films

Abstract: Pattern placement imprecision due to charging of the workpiece is believed to be a significant contribution to the total positional error in electron beam lithography. In an earlier work, Liu et al. [J. Vac. Sci. Technol. B 13, 1979 (1995)] reported that the surface potential of exposed resist could be negative or positive according to the resist thickness and the electron energy. In that work the authors were constrained to use a flood beam. In this study, we report a new independent approach using a Kelvin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Further, Liu et al 12 observed a positive surface potential at electron beam energies greater than 6 kV and a negative surface potential at electron beam energies smaller than 6 kV for a 0.4 m thick polybutene sulfone ͑PBS͒ and SAL601 resists coated on Cr/glass substrate. Recently, Bai et al 19 reported an increase in the positive surface potential with an increase in the beam energy and decrease in the resist thickness for PBS and UV5 resists on silicon substrate. According to these reports, when the resist thickness is smaller than the electron penetration depth, the trapped negative charge is negligible as the conducting substrate gives rise to image charges.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Liu et al 12 observed a positive surface potential at electron beam energies greater than 6 kV and a negative surface potential at electron beam energies smaller than 6 kV for a 0.4 m thick polybutene sulfone ͑PBS͒ and SAL601 resists coated on Cr/glass substrate. Recently, Bai et al 19 reported an increase in the positive surface potential with an increase in the beam energy and decrease in the resist thickness for PBS and UV5 resists on silicon substrate. According to these reports, when the resist thickness is smaller than the electron penetration depth, the trapped negative charge is negligible as the conducting substrate gives rise to image charges.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed to measure surface potentials (Liu et al, 1995;Bai et al, 1999;Mizuhara et al, 2002). The profile and value of surface potential were also simulated by electron scattering (Zhang et al, 2003) and a one-dimensional model (Yasuda et al, 2008), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5͑a͒ compares the dependencies on varying PBS thicknesses for 10 keV energy, a PBS/Si substrate and focused beam exposure. 8 Figure 5͑b͒ shows the results for varying beam energies, SAL601 ͑0.4 m͒/Cr͑0.085 m͒/glass substrate and flood beam exposure. 9 Figures 5͑a͒ and 5͑b͒ show the similar shapes between them.…”
Section: Resultsmentioning
confidence: 97%
“…Pease's a͒ Author to whom correspondence should be addressed; electronic mail: lyj@mintlab.snu.ac.kr group at Stanford University experimentally confirmed this theory. 8,9 We have assumed the amount of charge as fully constant ͑steady state͒ after a ''critical or relaxation time ͑͒.'' is given by…”
Section: Modeling and Calculation Proceduresmentioning
confidence: 99%